2017
DOI: 10.1021/acs.joc.7b00661
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic αγα-Tripeptides with Fluorinated- and Nonfluorinated-Furanoid Sugar Framework: Importance of Fluoro Substituent in Reverse-Turn Induced Self-Assembly and Transmembrane Ion-Transport Activity

Abstract: Acyclic αγα-tripeptides derived from fluorinated-furanoid sugar amino acid frameworks act as reverse-turn inducers with a U-shaped conformation, whereas the corresponding nonfluorinated αγα-tripeptides show random peptide conformations. The NMR studies showed the presence of bifurcated weak intramolecular hydrogen bonding (F···HN) and N···F charge-dipole attraction compel the amide carbonyl groups to orient antiperiplanar to the C-F bond, thus, demonstrating the role of the fluorine substituent in stabilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…More recently, Talukdar et al. discovered the importance of fluorination of the peptide backbones for their aggregation [86] . They reported that tripeptides with fluorine substituents presented a reverse‐turn U‐shaped conformation, whereas the non‐fluorinated counterparts only displayed disordered states.…”
Section: Supramolecular Artificial Anion Channelsmentioning
confidence: 99%
“…More recently, Talukdar et al. discovered the importance of fluorination of the peptide backbones for their aggregation [86] . They reported that tripeptides with fluorine substituents presented a reverse‐turn U‐shaped conformation, whereas the non‐fluorinated counterparts only displayed disordered states.…”
Section: Supramolecular Artificial Anion Channelsmentioning
confidence: 99%
“…Inspired by our recent ion transport studies with fluorinated acyclic and cyclic sugar derived peptides [1718], we investigated the ion transport activity of 1 and 2a across lipid bilayer membranes. In this study, the collapse of the pH gradient (pH out = 7.8 and pH in = 7.0), created across egg yolk ʟ-α-phosphatidylcholine (EYPC) vesicles with entrapped 8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt (HPTS) dye (i.e., EYPC-LUVsHPTS) [5761] was monitored by measuring the fluorescence intensity of the dye at λ em = 510 nm (λ ex = 450 nm) with time (Figure S11, Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last several years, synthetic peptides are known to play a significant role in the design of artificial ion transport systems [1316]. Recently, our group has synthesized fluorinated acyclic and cyclic peptides from C-3 fluorinated ᴅ-glucofuranoid amino acids and demonstrated their selective anion transport activity [1718]. In continuation of our interest in sugar-derived cyclic peptides [19], we aimed to synthesize cyclic peptides I and II from the corresponding linear di- and tetrapeptides, however, we obtained an oxazolone ring containing pseudo peptides 1 and 2a, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In separate work, backbone fluorination of cyclized tetra-and hexapeptides led to the formation of self-assembled nanotubes that serve as transmembrane anion-selective transporters. [36] Here, addition of fluorine atoms induced reverse turns that facilitated β-strand conformations and tubular assemblies, [36,72] for decades to promote and stabilize α-helical and β-hairpin conformations. [73][74][75][76] Similarly, phase-separated thin film electrodes have been realized by templating the assembly of an elastin-like peptide at the surface of a hydrophobic, perfluorinated ionomer.…”
Section: Methods Of Peptide Fluorination and Their Emergent Propertiesmentioning
confidence: 99%